BRAF V600E Status Sharply Differentiates Lymph Node Metastasis-associated Mortality Risk in Papillary Thyroid Cancer - Tao, Yubing; Wang, Fei; Shen, Xiaopei; Zhu, Guangwu; Liu, Rengyun; Viola, David; Elisei, Rossella; Puxeddu, Efisio; Fugazzola, Laura; Colombo, Carla; Jarzab, Barbara; Czarniecka, Agnieszka; et al. (The Journal of clinical endocrinology and metabolism, 2021)
CONTEXT: How lymph node metastasis (LNM)-associated mortality risk is affected by BRAF V600E in papillary thyroid cancer (PTC) remains undefined. OBJECTIVE: To study whether BRAF V600E affected LNM-associated mortality in PTC. DESIGN, SETTING, AND PARTICIPANTS: We retrospectively analyzed the effect of LNM on PTC-specific mortality with respect to BRAF status in 2638 patients (2015 females and 623 males) from 11 centers in 6 countries, with median age of 46 [interquartile range (IQR) 35-58] years and median follow-up time of 58 (IQR 26-107) months. RESULTS: Overall, LNM showed a modest mortality risk in wild-type BRAF patients but a strong one in BRAF V600E patients. In conventional PTC (CPTC), LNM showed no increased mortality risk in wild-type BRAF patients but a robustly increased one in BRAF V600E patients; mortality rates were 2/659 (0.3%) vs 4/321 (1.2%) in non-LNM vs LNM patients (P = 0.094) with wild-type BRAF, corresponding to a hazard ratio (HR) (95% CI) of 4.37 (0.80-23.89), which remained insignificant at 3.32 (0.52-21.14) after multivariate adjustment. In BRAF V600E CPTC, morality rates were 7/515 (1.4%) vs 28/363 (7.7%) in non-LNM vs LNM patients (P < 0.001), corresponding to an HR of 4.90 (2.12-11.29) or, after multivariate adjustment, 5.76 (2.19-15.11). Adjusted mortality HR of coexisting LNM and BRAF V600E vs absence of both was 27.39 (5.15-145.80), with Kaplan-Meier analyses showing a similar synergism. CONCLUSIONS: LNM-associated mortality risk is sharply differentiated by the BRAF status in PTC; in CPTC, LNM showed no increased mortality risk with wild-type BRAF but a robust one with BRAF mutation. These results have strong clinical relevance.
Keywords: Humans; papilární karcinom štítné žlázy; lidé středního věku; Proto-Oncogene Proteins B-raf; Biomarkers, Tumor; Female; mutace; dospělí; Thyroid Neoplasms; lidé; Lymphatic Metastasis; Thyroid Cancer, Papillary; lymfatické metastázy; nádorové biomarkery; Adult; protoonkogenní proteiny B-Raf; Follow-Up Studies; ženské pohlaví; lymph node metastasis; mortality; Male; prognostic molecular marker; Middle Aged; Retrospective Studies; risk stratification; prognóza; thyroid cancer; nádory štítné žlázy; retrospektivní studie; lokální recidiva nádoru; míra přežití; Mutation; mužské pohlaví; BRAF mutation; Neoplasm Recurrence, Local; Prognosis; následné studie; Survival Rate